2014
DOI: 10.1093/brain/awu349
|View full text |Cite
|
Sign up to set email alerts
|

Significance of neurovascular contact in classical trigeminal neuralgia

Abstract: Neurovascular contact is considered a frequent cause of classical trigeminal neuralgia and microvascular decompression with transposition of a blood vessel is preferred over other surgical options in medically refractory patients with classical trigeminal neuralgia. However, the prevalence of neurovascular contact has not been investigated in a representative cohort of patients with classical trigeminal neuralgia based in a neurological setting and using high-quality neuroimaging and blinded evaluation. We aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
159
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(175 citation statements)
references
References 35 publications
13
159
1
2
Order By: Relevance
“…The remaining 135 patients constitute the study population ( Figure 3). The clinical characteristics of the total patient population were described in previous papers (19,23), and the prevalence of NVC and its associated characteristics on the symptomatic and asymptomatic side was reported in a recently published paper (5). The evaluation of the NVC was uncertain on the symptomatic side in three cases and in five cases on the asymptomatic side.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 135 patients constitute the study population ( Figure 3). The clinical characteristics of the total patient population were described in previous papers (19,23), and the prevalence of NVC and its associated characteristics on the symptomatic and asymptomatic side was reported in a recently published paper (5). The evaluation of the NVC was uncertain on the symptomatic side in three cases and in five cases on the asymptomatic side.…”
Section: Resultsmentioning
confidence: 99%
“…This is of major importance to TN etiology and pathophysiology, and possibly also for selection of patients for microvascular decompression (MVD). However, approximately half of TN patients do not have a severe NVC on the symptomatic side (2)(3)(4)(5)(6). Furthermore, a simple NVC, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Severe neurovascular contact was defined as either displacement or atrophy of the trigeminal nerve on the symptomatic side at the site of an offending blood vessel. 16 All TN patients were requested to complete a Pain DETECT Questionnaire right before QST to obtain pain intensity ratings for subgroup analysis. The Pain DETECT Questionnaire is a validated screening tool developed in cooperation with DFNS.…”
Section: Medication Remission Neurovascular Contact and Pain Severitymentioning
confidence: 99%
“…Intraoperative microneurographic recordings in trigeminal nerve fibers after stimulation of the known trigger zone in a TN patient demonstrated afterdischarges that were absent when unaffected facial areas were stimulated (13), loss, demyelination and dysmyelination consistent with NVC of the trigeminal nerve (2). However, recent studies have suggested that only severe neurovascular contact, causing displacement or atrophy of the nerve, is associated with pain in classical TN (3,4), and some studies have questioned whether NVC is necessary and sufficient for TN, since pain can occur and recur in the absence of nerve compression (5,6). A recent study reported…”
mentioning
confidence: 96%